Typhoon Haiyan survivors at the resettlement sites: Covid-19 pandemic realities and challenges - Ladylyn Lim Mangada; Ginbert Permejo Cuaton (Elsevier, 2022)
More than 15 thousand households have been relocated in Tacloban North, Philippines, after typhoon Haiyan devastated the city in November 2013. While still recovering from the longer-term impacts of the typhoon, these households are currently enduring the impacts of the Covid-19 pandemic. This paper reports the contemporary realities and challenges Haiyan survivors face at the resettlement sites of Tacloban city, Philippines based on the inputs of 19 key informants we interviewed from September to November 2020. Our data reveal that Covid-19 exacerbated survivors' access to essential social services such as water, education/learning, and health care. The inadequate shelter space forces survivors to apply non-engineered house repairs or stay out of the house despite quarantine, lockdown, and physical distancing protocols. The pandemic has significantly increased survivors' livelihood insecurity resulting in a surging incidence of hunger, petty crimes, and neighborhood conflicts. This paper brings to the fore typhoon survivors' contemporary, precarious, and challenging conditions in resettlement sites. Almost ten years since Haiyan, this paper explores the extended pathways of Haiyan survivors' strained and uneven recovery hampered by the contemporary public health crisis that is the Covid-19 pandemic.